Cerebral oxygenation during hyperoxia-induced increase in exercise tolerance for untrained men - Oussaidene, Kahina; Prieur, Fabrice; Bougault, Valérie; Borel, Benoit; Matran, Regis; Mucci, Patrick (European journal of applied physiology, 2013)
This study aimed to investigate the involvement of cerebral oxygenation in limitation of maximal exercise. We hypothesized that O2 supplementation improves physical performance in relation to its effect on cerebral oxygenation during exercise. Eight untrained men (age 27 ± 6 years; VO2 max 45 ± 8 ml min(-1) kg(-1)) performed two randomized exhaustive ramp exercises on a cycle ergometer (1 W/3 s) under normoxia and hyperoxia (FIO2 = 0.3). Cerebral (ΔCOx) and muscular (ΔMOx) oxygenation responses to exercise were monitored using near-infrared spectroscopy. Power outputs corresponding to maximal exercise intensity, to threshold of ΔCOx decline (ThCOx) and to the respiratory compensation point (RCP) were determined. Power output (W max = 302 ± 20 vs. 319 ± 28 W) and arterial O2 saturation estimated by pulse oximetry (SpO2 = 95.7 ± 0.9 vs. 97.0 ± 0.5 %) at maximal exercise were increased by hyperoxia (P < 0.05). However, the ΔMOx response during exercise was not significantly modified with hyperoxia. RCP (259 ± 17 vs. 281 ± 25 W) and ThCOx (259 ± 23 vs. 288 ± 30 W) were, however, improved (P < 0.05) with hyperoxia and the ThCOx shift was related to the W max improvement with hyperoxia (r = 0.71, P < 0.05). The relationship between the change in cerebral oxygenation response to exercise and the performance improvement with hyperoxia supports that cerebral oxygenation is limiting the exercise performance in healthy young subjects.